p53 Interacts with RNA Polymerase II through Its Core Domain and Impairs Pol II Processivity In Vivo - Kim, Sunyoung; Balakrishnan, Sri Kripa; Gross, David S. (PLOS ONE, 2011)
The tumor suppressor p53 principally functions as a gene-specific transcription factor. p53 triggers a variety of anti-proliferative programs by activating or repressing the transcription of effector genes in response to genotoxic stress. To date, much effort has been placed on understanding p53's ability to affect transcription in the context of its DNA-binding activity. How p53 regulates transcriptional output independent of DNA binding is less well understood. Here we provide evidence that human p53 can physically interact with the large subunit of RNA polymerase II (Pol II) both in in vitro interaction assays and in whole cell extracts, and that this interaction is mediated (at least in part) through p53's core DNA-binding domain and the Ser5-phosphorylated CTD of Pol II. Ectopic expression of p53, combined with mutations in transcription elongation factors or exposure to drugs that inhibit Pol II elongation, elicit sickness or lethality in yeast cells. These phenotypes are suppressed by oncogenic point mutations within p53's core domain. The growth phenotypes raise the possibility that p53 impairs Pol II elongation. Consistent with this, a p53-dependent increase in Pol II density is seen at constitutively expressed genes without a concomitant increase in transcript accumulation. Additionally, p53-expressing yeast strains exhibit reduced transcriptional processivity at an episomal reporter gene; this inhibitory activity is abolished by a core domain point mutation. Our results suggest a novel mechanism by which p53 can regulate gene transcription, and a new biological function for its core domain that is susceptible to inactivation by oncogenic point mutations.